Upaya Hukum Notaris Atas Sanksi Pemberhentian Sementara Oleh Majelis Pengawas Pusat Notaris (Studi Putusan Nomor: 43/G/2011/PTUN-JKT) - Siregar, Khavieza; Ginting, Budiman; Devi, T. Keizerina (Mahesa Research Center, 2021)
This article or writing aims to reveal the form of solidarity of the Madurese community in Watu Ulo Hamlet in the Pethik Laut tradition/ceremony. Researchers took this location as a research point because based on previous research, the literature on social solidarity in traditional community traditions is still limited. In addition, the researchers also studied the Pethik Laut in Watu Ulo Hamlet, Ambulu, Jember because so far the research on the Pethik Laut in Jember is still small. The problem is focused on the form of social solidarity of the Madurese community in Watu Ulo when carrying out this tradition. To approach this problem, Emile Durkheim's theoretical reference on the concept of social solidarity is used. The data were collected through the synthesis of online interviews and literature study, and analyzed qualitatively. This study concludes that attachment to values and social reality also forms solidarity. For example, there is a form of social solidarity among the Madurese in this tradition, namely solidarity in determining and preparing ceremonies, such as withdrawing funds, making food, and managing activities. Thus, the social solidarity of the Madurese community is included in the Durkheim type of mechanical solidarity.